Long-Term Maternal Mental Health after Spontaneous Preterm Birth - Janssen, Laura E.; Laarman, Aranka R.C.; van Dijk-Lokkart, Elisabeth M.; Bröring-Starre, Tinka; Oudijk, Martijn A.; de Groot, Christianne J.M.; de Boer, Marjon A. (American Journal of Perinatology, 2023)
Objective The aim of this study is to investigate whether a history of spontaneous preterm birth (SPTB) is associated with maternal depressive and anxiety symptoms, or psychosocial distress in the fifth decade of life.Study Design This is a secondary analysis of the PreCaris-study, a prospective observational study in which we included 350 women with a history of SPTB between 220/7 and 366/7 weeks of gestation and compared them to 115 women who had a term birth. Primary outcomes were the Depression and Anxiety scores measured using the Hospital Anxiety Depression Scale and Psychosocial distress assessed with the Distress Thermometer for Parents. Secondary outcomes were self-reported impact of the birth in daily life and psychosocial support after delivery.Results After a median of 13 years after delivery, no significant differences were found in primary outcomes. Significantly more women with a history of SPTB reported that the birth still had impact in daily life; adjusted odds ratio: 2.46 (95% confidence interval: 1.35–4.48). A total of 57 (16.3%) women after SPTB reported to have needed professional psychosocial support after delivery but did not receive it. These women more often had a high Anxiety score (p = 0.030), psychosocial distress (p = 0.001), and influence of birth in daily life (p = 0.000).Conclusion There are no long-term effects on depressive and anxiety symptoms and psychosocial distress in women who experienced SPTB compared with women who had a full-term pregnancy. A significant part of the women who delivered preterm needed psychosocial support but did not receive it and were at higher risk of anxiety, psychosocial distress, and impact in daily life. We therefore recommend offering all women after SPTB psychosocial support after delivery.Key Points
Keywords: spontaneous preterm birth; depression; depressive symptoms; anxiety; psychosocial distress